The Effect of Sargassum Extract on Culture Medium to The Growth of Chaetoceros gracilis - Malik, Andi Adam; Khaeruddin, Khaeruddin; Fitriani, Fitriani (Indonesian Aquaculture Society (MAI), 2018)
Hatchery is one of important factors to maximize shrimp production. One of supporting factorsis the availability of qualified natural foodsin sufficient quantities.The aim of this study was to know the addition effect of extract Sargassum to culture medium for population growth of Chaetoceros gracilis. Culture medium used for microalgae C. grasilis was a 12 liter jar with density of 105 cell/mL. The Sargassum extract was obtained by processing Sargassum waste through anaerob fermentation, then was extractedand considered as liquid organic fertilizer. Tested treatment was A = 0 ppm (without Sargassum extract), B = 10 ppm of Sargassumextract, C = 20 ppm of Sargassumextract andD =30 ppm of Sargassumextract for three replications. It was found that the population density of C. gracilis increased and the highest algae density occurred in treatmentD on day5, followed with C, B and A, which were 353,433 cell/mL, 336,833 cell/mL,308,867 cell/mL and 244,433 cell/mL. This illustrates that the addition of high doses has affected the population density of microalgae C.gracilis.